Assets (Nominated play, excerpt) - Georgieva, Theodora (Sledva : NBU Journal of Humanities and Arts, 2020)
A dystopian play representing a world based entirely on the number of assets people have. (Assets - points equal to the cash owned by each person.) People accumulate assets since childhood; the number of their assets determines their education, access to food, medicines, work. The main conflict is between the material represented by the Branch Managers who direct the assets flow, and the spiritual, represented by those who oppose them. The play is set in a city recently taken by the Branch. The new government promises progress and better life and most people support it. But there are others who disagree because they cannot stand the prohibition of music, books, parties.